UTICAJ 6-MESEČNOG PROGRAMA TRČANJA NA IZDRŽLJIVOST I PARAMETRE AEROBNE EFIKASNOSTI KOD ODRASLIH LJUD - Branko Škof; Radoje Milić; Mateja Fabjanič (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
Preventing a decrease in aerobic capacity in middle age and later through regular physical activity, is the key task of preventive gerontology. The study aimed to establish the effect of a complex, 24-week recreational running programme on endurance (running fitness) and the physiological and biochemical parameters of aerobic efficiency of people in medium and late-middle age. The study involved 25 women and 22 men of an average age of 42.5 ± 10.3 years (from 27 to 63 years) and of very different physical conditions. After the 24-week training, the runners' VO2max improved by 10.4% and 8.9%, respectively; (P < 0.001), whereas their endurance improved by 17.1% (P < 0.001). The improvement in the runners' aerobic capacity was mainly due to the increase in the heart stroke volume by 9.2%, (P < 0.05) and to a smaller extent to A-V dif.